Impact ionization and the paradox of defects in transition metal dichalcogenide FETs - Rupali Verma; Utpreksh Patbhaje; Asif A. Shah; Aadil Bashir Dar; Mayank Shrivastava (npj 2D Materials and Applications)
Abstract For developing high-performance, reliable, and robust electronic devices, fundamental analysis of the hot carrier dynamics, high field transport, and electrical breakdown mechanisms in transition metal dichalcogenide field effect transistors is essential, which is largely unknown. In this paper, using a combination of electrical measurements, high-field spatial electroluminescence measurements, and theoretical models, it is presented that the impact ionization in MoS2 is mediated via defects, i.e., assisted via defect-induced trap states. Several unique observations, such as threshold voltage left-shift, increased subthreshold slope, anticlockwise hysteresis in the output characteristics, and bias-dependent redistribution of the electric field, are recorded when biased in the impact ionization regime, which we discover is due to the field-dependent dynamic occupancy of the defect states. Finally, we confirm a unified mechanism of high field breakdown as a competition between avalanche breakdown and minority carrier injection-induced breakdown from the variation of spatial electroluminescence with the gate voltage.